Robot-assisted laparoscopic surgery for abdominal metastatic melanoma mimicking a gastrointestinal stromal tumor: A case report and review of the literature. Issue 26 (June 2018) - Ye, Zhou; Yang, Zhe; Zheng, Shusen; Wang, Weilin
Abstract: Rationale: Uveal melanoma is the most common primary intraocular malignancy, which could metastasize at an early stage of the disease and associated with poor prognoses. Liver, small bowel, stomach, and colon are the most common locations for metastatic visceral melanoma, however, solitary abdominal metastasis from uveal melanoma is extremely rare. Patient concerns: The current study reports the case of a 33-year-old man with history of treated choroidal melanoma of the left eye that developed metastasis to the abdomen, preoperative endoscopic ultrasonography and computed tomography strongly suggested as a gastrointestinal stromal tumor (GIST). Diagnoses: The patient was diagnosed with abdominal metastatic melanoma according to his medical history and histopathological results. Interventions: The young adult underwent robot-assisted laparoscopic surgery. Outcomes: The patient finally got the definite diagnosis with his medical history and histopathological results and he has been living disease free for nearly 3 years after the surgery. Lessons: Although rare, the possibility of abdominal metastatic melanoma presenting with the clinical picture of gastrointestinal stromal tumor must be always considered by the surgeon especially the patients with a history of primary malignant melanoma.